A probabilistic method for certification of analytically redundant systems - Hu, Bin; Seiler, Peter (Zielona Góra: Uniwersytet Zielonogórski)
Analytical fault detection algorithms have the potential to reduce the size, power and weight of safety-critical aerospace systems. Analytical redundancy has been successfully applied in many non-safety critical applications. However, acceptance for aerospace applications will require new methods to rigorously certify the impact of such algorithms on the overall system reliability.
Keywords: avionics, certification; safety-critical systems; reliability; fault detection; fault-tolerant systems